Arrhenius Plot Analysis, Temperature Coefficient and Q10 Value Estimation for the Effect of Temperature on the Rate of Molybdenum Reduction by Acinetobacter calcoaceticus strain Dr.Y12 (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
Molybdenum is a micronutrient that is required as a co-factor for a variety of hydroxylation and redox transfer activities in both animal and plant physiological processes. The potential of over exposure to interfere with the sperm production and egg formation processes in a number of species, including fish, is the biggest danger of excessive exposure. Only recently has it been discovered that it can be utilised as a remediation method for molybdenum-reducing bacteria. The effect of temperature on molybdenum reduction is one of the variables to consider. It is possible to use many different models to estimate the growth rate of microbes on various media based on the temperature being utilised. The Arrhenius model is popular due to the fact that it contains a limited number of parameters. In general, temperature has an effect on the development and metabolic activity of microorganisms on their substrates. Because microorganisms are so tiny, they are very sensitive to changes in their environment's temperature. Growth on molybdenum by Acinetobacter calcoaceticus strain Dr.Y12 is described, with a discontinuous chevron-like graph of apparent activation energy with a breakpoint at 32.66 oC. Regression analysis results suggest that in the lower temperature range of 20-30 oC, growth on molybdenum had an activation energy of 66.48 kJ/mol, whereas at the higher temperature range of 37–45 oC, it had an activation energy of 99.5 kJ/mol. For the examined temperature range (20-30 oC) and (37-45 oC), Q10 values of 2.46 and 3.37 and theta values of 1.09 and 1.13 were obtained, respectively. This is study is very useful in predicting the breakdown of molybdenum and the movement of molybdenum during bioremediation.
Keywords: Molybdenum-degrading; Acinetobacter calcoaceticus strain DrY12; temperature; Arrhenius plot; breakpoint